The effect of mango and neem extract on four organisms causing dental caries: Streptococcus mutans, Streptococcus salivavius, Streptococcus mitis, and Streptococcus sanguis: An in vitro study - Prashant G; Chandu G; Murulikrishna K; Shafiulla M (Wolters Kluwer Medknow Publications, 2007)
Background and Objectives: Chewing twigs of the mango or neem tree is a common way of cleaning the teeth in the rural and semi-urban population. These twigs are also believed to possess medicinal properties. The present study was conducted to evaluate the antimicrobial effects of these chewing sticks on the microorganisms Streptococcus mutans , Streptococcus salivarius , Streptococcus mitis , and Streptococcus sanguis which are involved in the development of dental caries. An additional objective was to identify an inexpensive, simple, and effective method of preventing and controlling dental caries. Materials and Methods: The sticks were sun dried, ground into a coarse powder, and weighed into 5 gm, 10 gm, and 50 gm amounts. These were added to 100 ml of deionized distilled water. After soaking for 48 h at 4°C, the water was filtered. The filtrate was inoculated onto blood agar plates containing individual species of microorganisms and incubated at 37°C for 48 h. Results: Mango extract, at 50% concentration, showed maximum zone of inhibition on Streptococcus mitis . Neem extract produced the maximum zone of inhibition on Streptococcus mutans at 50% concentration. Even at 5% concentration neem extract showed some inhibition of growth for all the four species of organisms. Interpretation and Conclusion: A combination of neem and mango chewing sticks may provide the maximum benefit. We recommend the use of both the chewing sticks.